Produkcja energii z biomasy rolniczej a pojęcie działalności rolniczej w prawie włoskim i francuskim - Paquel, Kamila (Wydawnictwo Naukowe UAM, 2013)
The concept of agricultural production in Italy as well as in France has been relatively broad and it includes the use of biomass for energy production, which largely originates from own agricultural production. The introduction of a modern definition of agricultural production that includes utilisation of certain forms of biomass for energy purposes helps to eliminate potential concerns when it comes to situation like qualification of agricultural land on which agricultural bio-gas plants are located, or recognition of such plants or bioenergy equipment as belonging to a given agricultural farm. The legal regulations analysed in the paper account for the concept of multifunctional agriculture and permit agricultural producers to maintain their privileged status when they engage in a production of energy from renewable sources.Challenges of counteracting climate change in order to maintain territorial balance constitute the basic premises for integrating ‘new’ forms of agricultural activity with the traditionally understood categories existing in agricultural law, including the concept of agricultural activity.

In Italia, come in Francia, vige un concetto assai ampio di attività agricola, in esso è inclusa l’attività consistente nell’utilizzo della biomassa proveniente in maggioranza dalla produzione agricola propria a fini energetici. L’introduzione della moderna definizione di attività agricola, la quale abbraccia alcune forme di utilizzo della biomassa a fini energetici, permette tra l’altro di dissipare i dubbi circa la qualificazione dei terreni agricoli, sui quali vengono collocati p.es. impianti agricoli di biogas e circa l’appartenenza delle attrezzature e delle strutture bioenergetiche all’azienda agricola. Le regolazioni giuridiche sottoposte all’analisi sono conformi alla concezione di agricoltura multifunzionale; esse consentono ai produttori agricoli di mantenere uno status privilegiato nel caso in cui svolgono attività di produzione dell’energia da fonti rinnovabili. Le sfide connesse alla necessità di controbilanciare i cambiamenti climatici e di mantenere l’equilibrio territoriale costituiscono delle premesse fondamentali per l’integrazione delle menzionate „nuove” attività con le categorie di diritto agrario tradizionalmente intese, tra cui tra l’altro con il concetto di attività agricola.
Production of Agricultural Biomass Energy vs the Concept of Agricultural Activity in Italian and French Laws
La Produzione di Energia da Biomasse Agricole e il Concetto di Auuività Agricola nel Diritto Italiano e Francese